La Découverte De La Fonction Logarithme En Utilisant Les Suites Et Le Logiciel Geogebra - Sbaa Mohammed El aydi M’hamed; Radi Bouchaib; Naceur Achtaich (European Scientific Journal, ESJ, 2017)
Mathematics Logarithmic functions are an important part of the school curriculum. Also, they are important tools for solving problems in mathematics, physics, chemistry, biology, economics etc. The teaching of these functions is done in different ways in school curricula. This article focuses on the discovery of logarithmic functions using alternative methods for efficient didactic transposition. Our work focuses on: A bit of history concerning the invention of the logarithm function; Demonstration of the existence of a function which transforms the product in sum; Discover the logarithm function using the GeoGebra software; Explore the parameters of the function f (x) = a logb (x + h) + k using the GeoGebra software; Application of the GeoGebra software to solve problems containing the logarithm function. We concluded this work by clarifying the usefulness of the Geogebra tutorial in the didactic transposition for the teaching of logarithmic functions for the pupil as well as for the teacher. Also, this study assesses students' motivation in learning mathematical concepts. In addition, we propose didactic perspectives of the use of Geogebra in improving the teaching of mathematics.